HUMAN-AI COLLABORATION IN ENGINEERING MANAGEMENT: LEVERAGING MACHINE INTELLIGENCE FOR DECISION-MAKING, WORKFLOW AUTOMATION, AND INNOVATION - Muhammad Mashal Khattak; Behram Ayub Khan; Waqar Aslam; Ali Raza (Spectrum of Engineering Sciences, 2025)
This paper focuses on the use of artificial intelligence in the field of engineering management to improve decision making processes, rationalize organizational operations and promote innovation. Advanced technologies including machine learning and advanced analytics are already being used to introduce more accurate data for forecasting, risk evaluation as well as allocation of resources in engineering projects. The combination of human and artificial intelligence is presented as a mutually beneficial process: AI helps engineers to make better decisions based on data, as well as solve routine tasks which allows for better creative thinking. The paper also reveals some of the biggest barriers of applying AI, such as the scarcity of qualified talent, high costs of placing AI into practice, and resistance to change. However, with the progression of AI as well as other advanced technology such as IoT and cloud computing, engineering management can stand to benefit greatly in terms of efficiency of practices and advancement in innovation.